H∞ dynamic output feedback control for a networked control active suspension system under actuator faults. (1st January 2022) - Viadero-Monasterio, Fernando; Boada, B.L.; Boada, M.J.L.; Díaz, V.
Abstract: This paper presents an investigation of the event-triggered control problem for an active suspension system featuring a networked communication architecture and Dynamic Output Feedback Controller (DOFCs) while taking into account the possibility of failure in actuators. The event-triggering condition determines when it is necessary to transmit the observed variables of the plant to the controller, in order not to saturate the network. A Dynamic Output Feedback Controller is synthesized under LMI restrictions to guarantee the system stability with the H ∞ criteria, using the Lyapunov–Krasovskii functional approach. As the failures in actuators affect the state space model of the system, a novel polytopic model is employed to approach the plant function. In order to prove a practical feasibility, control performance characteristics for vibration suppression are evaluated under various road conditions. Highlights: Actuator failure is modelled through a polytopic model. To reduce the networked data transmission, an Event-Triggered law is used. Ride comfort and road holding are simultaneously improved.